The complex research on the technical conditions of energy application of wood pyrolysis bio-oil - Larionov K. B. Kirill Borisovich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Kirgina M. V. Mariya Vladimirovna; Gvozdyakov D. V. Dmitry Vasilievich; Zenkov A. V. Andrey Viktorovich; Bogdanov I. A. Ilya Aleksandrovich; Kaltaev A. Albert; Gubin V. E. Vladimir Evgenievich (2022, 2022)
Title screen